Molecular Basis of Two‐Exon Skipping (Exons 12 and 13) by c.1248+5g>a in OXCT1 Gene: Study on Intermediates of OXCT1 Transcripts in Fibroblasts. Issue 3 (22nd January 2013) - Hori, Tomohiro; Fukao, Toshiyuki; Murase, Keiko; Sakaguchi, Naomi; Harding, Cary O.; Kondo, Naomi
<x xml:space="preserve">Abstract</x> An IVS13 mutation (c.1248+5g>a) of the OXCT1 gene resulted predominantly in skipping of exons 12 and 13 in fibroblasts. Analysis of intermediates of OXCT1 transcripts in control fibroblasts showed that intron 11 was the last intron to be spliced and intron 12 removal occurred after intron 13 removal in the major pathway. Retention of the mutated intron 13 in the patient's fibroblasts causing retention of introns 12 and 11 resulted in the two exon skipping due to "splicing paralysis". <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>